THE CONCEPTUALIZATION OF HAPPINESS USING FORCE IMAGE SCHEMA IN HUNGER GAMES TRILOGY BOOKS: COGNITIVE SEMANTIC STUDIES - Dean Raiyasmi; Puspita Sari (English Journal Literacy Utama, 2020)
This research analyses the conceptualization of happiness using force image schema in hunger games trilogy books. This research is aimed at elaborating how the process of conceptualizing happiness by using force image schema and analyzing force image by using image schema and other image schema that plays an important role in determining happiness itself as force. The method used in this research is descriptive analysis method. The data are elaborated and described by using conceptual metaphor and force image schema. The results of the conceptualization of happiness using force image schema are occurred due to the lexical items used in each data. Even though these data are classified as happiness using force image schema, each data has different process due to the lexical items used in each sentence. Moreover, one of the data shows a complicated process which involves several image schemas to create a concept of happiness as force.